Magnetic Resonance Therapy (MRT) and Relativistic Effect of Rotation (Global Journals of Research in Engineering, 2025)
Epoxide within molecular structures is recognized as hallmarks of potent carcinogenic cells This paper proposes a novel approach Magnetic Resonance Therapy MRT which selectively eliminates epoxide in cancerous tissues while preserving oxygen in healthy tissues offering a potentially side-effect-free method for cancer treatment and prevention The study presents a series of in vitro in vivo and clinical experiments to support this innovative therapeutic strategy The underlying mechanism of MRT is grounded in the principles of relativity for rotational frames and an experimental validation of this theoretical framework is provided Furthermore this research unveils previously undescribed relativistic phenomena including space-time exchange critical cylinder effects strong and sub-strong and weak interactions as well as the source of quantum property and the source of mass as well as dark mas Due to space constraints the detailed mechanism of epoxide elimination will be elucidated in a subsequent publication
Keywords: cancer; epoxide; magnetic resonance therapy; relativity for rotational frames